Diffusion in velocity of charged particles scattering the electromagnetic wave - Ognivenko, V.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The scattering of an external monochromatic electromagnetic wave by identical charged particles is considered, the influence of the scattered radiation on particles motion being taken into account. The diffusion in velocity of particles caused by their collisions and fields of the scattered radiation is investigated. The mean-square spread in the velocity of particles is determined as a function on time, parameters of external electromagnetic wave and the system of the charged particles. Рассмотрено рассеяние внешней монохроматической электромагнитной волны идентичными заряженными частицами с учетом влияния рассеянного излучения на движение частиц. Исследована диффузия по скоростям частиц, вызванная столкновениями частиц и полями рассеянного излучения. Установлена зависимость среднеквадратичного разброса частиц по скоростям от времени, параметров волны и системы заряженных частиц. Розглянуто розсіяння зовнішньої монохроматичної електромагнітної хвилі ідентичними зарядженими частинками з урахуванням впливу розсіяного випромінювання на рух частинок. Досліджено дифузію по швидкостям частинок, що викликана зіткненнями частинок і полями розсіяного випромінювання. Встановлено залежність середньоквадратичного розкиду частинок по швидкостях від часу, параметрів хвилі і системи заряджених частинок.